Realising Sedgwick's vision: theorising strategies of resistance to neoliberal mental health and welfare policy. (18th November 2016) - Moth, Rich; McKeown, Mick
Abstract : There has recently been renewed interest in non-reductive historical materialist modes for analysing social movements, of which the work of mental health activist and Marxist theorist Peter Sedgwick is a precursor. We contend that Sedgwick's approach retains contemporary utility for theorising radical mental health movements, though we argue that this needs extension in light of intervening debates regarding the interaction of material and post-material concerns. Having established this, we will turn to an overview of recent neoliberal labour market, welfare and mental health policy reforms as a basis for consideration of the strategic implications for resistance and coalition building among survivor and worker activists. We will propose a contemporary Sedgwickian 'transitional' strategy as a means to realise transformative change in services and society. In conclusion, we argue that tools for promoting this strategy, such as the Social Work Action Network's 'Mental health charter', may assist in binding together diverse constituencies to strengthen alliances of resistance.